Sexual Equality Under the Fourteenth and Equal Rights Amendments - Ruth Bader Ginsburg (Washington University Law Quarterly, 1979)
This Article discusses the two rubrics under which gender-based classifications in the law might be tested: first, the equal protection principle explicit in the fourteenth amendment and implicit in the fifth amendment; and second, the sex equality principle presented in the proposed Equal Rights Amendment.
Keywords: Constitutional amendments; Sex discrimination; Equal protection; Equal Rights Amendment